Effect of Injector Timing Variations Using a Programmable ECU on Exhaust Gas Emissions of FI Motorcycles - Firmansyah M. Sadly; Saputra Riko; Febriansyah Ilham; Khopipah Siti; Al Afgani Jamaluddin; Purwanto Wawan; Maksum Hasan (E3S Web of Conferences)
The increase in motorcycle use in Indonesia has led to an increase in motorcycle production and technology owned by each motorcycle manufacturer and increased air pollution. With this increase, automotive manufacturers are competing to produce motorcycles that still use fossil fuels that are environmentally friendly. This problem can be reduced by implementing a fuel injection system that is electronically regulated by an electronic control unit to obtain the ideal fuel and air mixture. Therefore, this study aims to observe the effect of variations in injector timing using a programmed ECU on exhaust emissions. The results showed that the use of a programmed ECU was able to reduce exhaust emissions. The largest reduction in CO emissions occurred at 350˚ injector time of 1.59% at idle speed. The largest reduction in CO2 emissions occurred at 350˚ injector time of 3.33% at idle rotation. While the largest reduction in HC emissions occurred at 365˚ injector time of 162.3 ppm at idle speed.